Implementasi Aplikasi Quipper School dalam Pembelajaran Daring dan Pembelajaran Tatap Muka Terbatas Pada Mata Pelajaran Geografi di SMAN 13 Semarang (Edu Geography, 2022)
This study aims to determine the implementation of the Quipper application, the obstacles and efforts in online learning and face-to-face learning is limited to geography subjects at SMAN 13 Semarang. Researchers collect data by using interviews, observation, and documentation. The data analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. The results show that the implementation of the Quipper School Application in learning geography at SMAN 13 Semarang has been going quite well since 2020 and is effectively used as a learning medium that can be used in the classroom and at home. Even when using the Quipper application, students are interested in learning and the content of the material is incomplete, even though the reading is long and a lot. Efforts to overcome teacher obstacles by maximizing the services available on the Quipper School Application, explaining to students the contents of the material are incomplete and reminding students to complete the assigned tasks while what students do in overcoming obstacles is to keep doing the tasks given by the teacher even though the material is and the video is too long, and students ask the teacher for material they have not understood. The conclusion in this study is that the implementation of the Quipper application in online learning and face-to-face learning is limited to geography subjects, starting from the preparation of learning tools to assessment using the Quipper school application.